The Concept of Generalised Syllabi of the Discipline «Foreign Language» for Non-Linguistics Major Courses of Study - M. M. Bazhutina; A. V. Tsepilova (Высшее образование в России)
The paper raises the issue of the relevance of creating generalized syllabi for each enlarged group of majors, when teaching linguistic disciplines of compulsory and optional parts of the curriculum related to the subject area «Foreign Language». The authors show the need for generalized syllabi as being grounded by existing controversies in modern foreign language training. The paper suggests a concept that substantiates the demand for targeted generalized syllabi for this discipline and contains a number of principles, which can help to design their optimal content. The notions of «zones of near and further content and competence integration» are introduced. The content of these zones is revealed, and their role in modelling the key components of generalized syllabi is shown. Integrated foreign language professional communicative competence of an engineering graduate is introduced as a prospective model of foreign language competence. It is regarded as an integrative notion combining traditional components of communicative competence with professional knowledge, skills and experience involved in the process of mastering cross-cultural professional communication. The realization of the concept principles in the content of generalized syllabi aims at the reflection of university graduates’ real foreign language communication needs in their professional activity in learning outcomes in accordance with the FSES HE 3 ++. The authors express certainty that the concept of generalized syllabi will allow to initiate the process of their creation and will become a stimulus to the development of foreign language teaching methodology in a non-linguistics university.